2016
DOI: 10.1371/journal.pone.0154523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malnutrition on Left Ventricular Mass in a North-Malagasy Children Population

Abstract: BackgroundMalnutrition among children population of less developed countries is a major health problem. Inadequate food intake and infectious diseases are combined to increase further the prevalence. Malnourishment brings to muscle cells loss with development of cardiac complications, like arrhythmias, cardiomyopathy and sudden death. In developed countries, malnutrition has generally a different etiology, like chronic diseases. The aim of our study was to investigate the correlation between malnutrition and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
3
19
0
1
Order By: Relevance
“…An additional finding of this study was that Malagasy children showed a significant longer QT/QTc interval compared to the Caucasians. As we previously reported [23], malnutrition was common among Malagasy children included in this study. It is possible that malnutrition might cause some changes in the cardiac repolarization, leading to a prolongation of the QT interval [24].…”
Section: Discussionsupporting
confidence: 59%
“…An additional finding of this study was that Malagasy children showed a significant longer QT/QTc interval compared to the Caucasians. As we previously reported [23], malnutrition was common among Malagasy children included in this study. It is possible that malnutrition might cause some changes in the cardiac repolarization, leading to a prolongation of the QT interval [24].…”
Section: Discussionsupporting
confidence: 59%
“…As demonstrated previously, 18 , 31 , 32 , 33 we found evidence of reduced myocardial mass. However, when adjusted for BSA, 34 few significant differences relative to reference values were evident. Similarly, the prevalence of abnormal cardiac function indices, when stratified by BSA, was proportionate to published cutoff levels.…”
Section: Discussionmentioning
confidence: 91%
“…All twenty-two included studies were cross-sectional by design, and each of the studies focused on the different geographic settings, distributed across four regions of the sub-Saharan Africa (see Figure 2). A large proportion of the studies (n = 10 studies) was conducted in urban settings, [24][25][26][27][28][29][30][31][32][33] and four studies were conducted in rural settings only. [34][35][36][37] One study was conducted in a periurban 38 and one study in a semi-rural setting.…”
Section: A) Study Participants and Geographical Settingmentioning
confidence: 99%
“…[40][41][42][43][44][45] Overall, the studies selected for inclusion (n = 22 studies) involved a total of 26 609 participants, 12 453 (46.8%) participants were males, and one study recruited only women of reproductive age living in informal settlements in Accra, Ghana 29 . The distribution of the rest of the studies by countries was as follows: 4 from Ethiopia, 25,27,40,41 ; 1 Nigeria, 24 ; 1 Madagascar, 26 ; 3 Ghana, 29,38,39 ; 1 Zambia, 37 ; 2 Tanzania, 28,35 ; 1 Malawi, 34 ; 1 Cameroon, 33 ; 2 Sudan, 30,31 ; 1 Burkina Faso, 42 ; 1 Kenya, 32 ; 1 Botswana, 45 and 3 studies from South Africa 36,43,44 . Figure 2 shows the study distribution from the four regions of sub-Saharan Africa, with only 1 study from Central Africa 33 and…”
Section: A) Study Participants and Geographical Settingmentioning
confidence: 99%
See 1 more Smart Citation